Beyond ‘manualistic’: The complex ontological status of the refug(e)e in the camps when the temporary becomes permanent - Canteiro Neto, Maria de Fátima; Goycoolea Prado, Roberto (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2024)
The institutionalization of human displacement, ratified with the creation of the United Nations High Commissioner for Refugees (1951), although effective in emergencies, However, it has had the unforeseen effect of prolonging situations that were conceived and programmed as temporary. This has raised questions about the nature of its action and has led to various limitations and dilemmas in asylum spaces, such as camps, indebted to a ‘manualistic’ approach that compresses life and architectural practice into instrumental indicators. The physical and legal dependence of refugees on the circumstances and decisions of the host states forces us to frame the discussion on refugees, and by extension, on refuge, as ontological problems. From this perspective, the proposed critical elaboration is that the evolution of the concept of reception spaces (or territories), as a physical manifestation of a political technology embodied in ‘manualistic’ practices, shapes an experience and management of refugee individuals that blurs their ontological status. This situation arises from the institutionalization of refuge and the consequent physical and legal dependence of refugees on external decisions. An ontological questioning of the refugee that, as we understand it, necessitates a reconsideration of the architecture and planning of refuge spaces.
Keywords: Refugees; Refugee Camps; ontology; Architecture and Planning; Protection